Development of Pocket Book-Based Teaching Materials on Japanese Occupation Material in Indonesia to Improve Understanding of Class XI Students at SMAN 3 Pekanbaru - Gustina, Vika; Ahmal, Ahmal; Asril, Asril (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Learning resources are basically used to make it easier for students and teachers to carry out the process of teaching and learning activities. During initial observations at SMAN 3 Pekanbaru, researchers received information from subject teachers that students' understanding of history lessons was still lacking. To make it easier and quickly improve students' understanding of learning, it would be better if learning resources were packaged in a concise form with clear material content and arranged using language that is not too rigid and easy to understand. It is even more practical if the learning resource is not too big and easy to carry, for example a pocket book. This research aims to develop teaching materials as a learning resource based on pocket books as an effort to increase students' understanding of history, especially regarding the Japanese occupation of Indonesia. The development method used is Research and Development (RnD) which involves planning, development and evaluation stages. The main finding of this research is that it shows that pocket book-based teaching materials are effective in increasing students' understanding of material about the Japanese occupation in Indonesia. The implication of the results of this research is that teaching materials are so important to help students improve their understanding of learning materials. The advantage of this pocket book is that it makes it easier for students to study anytime and anywhere. Apart from that, this pocket book-based teaching material also has shortcomings, namely in terms of writing size and color.